A Novel Hydrogen Peroxide Sensor via the Direct Electrochemistry of Horseradish Peroxidase Immobilized on Colloidal Gold Modified Screen-printed Electrode - Huangxian Ju; Songqin Liu; Xiaoxing Xu (Sensors, 2003)
The direct electrochemistry of horseradish peroxidase (HRP) immobilized on a colloidal gold modified screen-printed carbon electrode (HRP-Au-SPCE) and its application as a disposable sensor were studied. The immobilized HRP displayed a couple of stable and well-defined redox peaks with a formal potential of Ã¢Â€Â“0.338 V (vs. SCE) and a heterogeneous electron transfer rate constant of (0.75Ã‚Â±0.04) s-1 in 0.1 M pH 7.0 PBS. It showed a highly thermal stability, fast amperometric response and an electrocatalytic activity to the reduction of hydrogen peroxide (H2O2) without the aid of an electron mediator. The biosensor exhibited high sensitivity, good reproducibility, and long-term stability for the determination of H2O2 with a linear range from 0.8 ÃŽÂ¼M to 1.0 mM and a detection limit of 0. 4 ÃŽÂ¼M at 3ÃÂƒ. The variation coefficients are 2.7 % and 2.3 % for over 10 successive assays at the H2O2 concentrations of 8.0 and 20 ÃŽÂ¼M, respectively. The K M app for H2O2 sensor was determined to be 1.3 mM.